Կրթական գործի կազմակեպման հարցը Իրանի հայօճախում - Մկրտչեան, Կարէն (տպ. Atlas)
At the beginning of the 21st century, the network of Iranian Armenian schools faced numerous challenges that required large efforts and resources from the relevant educational boards. The fall in number of the Armenian community as a result of emigration i s making these efforts more and more difficult. The efforts are meant to maintain the competitive edge that the Armenian schools have over Iranian schools or at least to maintain the same level. In fact, legally there are no Armenian schools in Iran since all schools in the country are de jure included in the general system of public education. Thus, the concerns of the Armenian schools should be assessed in this context. Looking at the case from this perspective poses the problem of shaping a curriculum which is both in line with the state educational curriculum and at the same time addresses the specific mission of the Armenian schools. One needs to add the challenges su ch a curriculum faces rega rding the need for the creation of a relevant psychological and sociological atmosphere which is in harmony with Armenian identity. Alongside these challenges the paper highlights other institutional and administrative challenges like the appointment of no n-Armenian inspectors and headteachers, as well as financial worries regarding the salaries of the teachers, balancing the budget of the schools and generally the educational expenses of the Armenian schools.
Keywords: Պատմութիւն; Կրթութիւն; Հայ գաղթօջախներ; Իրան